Copper(II) and iron(III) complexes with arylhydrazone of ethyl 2-cyanoacetate or formazan ligands as catalysts for oxidation of alcohols - Martins, Nuno (2021)
The aquasoluble [Cu(1 kappa N,O-2:2 kappa O-HL1)(S)](2) [S = CH3OH (1), (CH3)(2)NCHO (2)] and [Cu(kappa N-HL1)(en)(2)]center dot CH3OH center dot H2O (3) Cu-II complexes were prepared by the reaction of Cu-II nitrate hydrate with the new ligand (E/Z)-4-(2-(1-cyano-2-ethoxy-2-oxoethylidene)hydrazinyl)-3-hydroxybenzoic acid (H3L1), in the presence (for 3) or absence (for 1 and 2) of ethylenediamine (en), while the Fe-III complex [Fe(kappa N-3-HL2)(2)] (4) was isolated by treatment of iron(III) chloride hexahydrate with the new ligand (1E,1E)-N',2-di(1H-1,2,4-triazol-3-yl)diazenecarbohydrazonoyl cyanide (H3L2), and characterized by elemental analysis, IR spectroscopy and single crystal X-ray diffraction. Cooperative E,Z -> E isomerization of H3L1, induced by coordination and ionic interactions, occurs upon interaction with Cu-II in the presence of en. Complexes 1-4 act as catalyst precursors for the solvent-free microwave (MW) assisted selective oxidation of primary or secondary alcohols and diols to the corresponding aldehydes, ketones and diketones, respectively, with yields in the 5-99% range (TONs up to 4.96 x 10(2)) after 60 min of MW irradiation at 120 degrees C. The influence of temperature, time and organic radicals was studied and also the regioselective oxidation of the catalytic systems involving the primary and secondary alcohols.